DETERMINAN KEJADIAN KARIES GIGI PADA PASIEN UMUR 18-40 TAHUN YANG BERKUNJUNG DI BP GIGI DI PUSKESMAS KELAYAN TIMUR KOTA BANJARMASIN DETERMINANT PREVALENCE OF KARIES - Deni Suryanto; Gusti Evi Zaidati; Fahrurazi Fahrurazi (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Research aims to understand determinants associated with dental caries incidence in patients age 18-40 years in dental treatment center at public health center kelayan timur district south banjarmasin. This research is an analytic observation with Cross Sectional design, while the population in this study is all patients who went to dental treatment center at puskesmas Kelayan Timur, during the research that took place from June to July 2012. Sampling in this research is done by accidental sampling technique, where the sample is taken from the respondent or the case that happened to exist at the time of research. Samples in this study were all dental caries patients aged 18-40 years who went to dental treatment center during the study which amounted to 48 people. Data collection by interviewing directly with respondents using questionnaire. Data analysis using Chi Square test. The results of the research is known There is no significant relationship between education and knowledge of respondents with dental caries incidence in patients aged 18-40 years who visited in dental treatment center at Puskesmas Kelayan Timur District Banjarmasin Selatan. There is a significant relationship between the frequency of brushing teeth with dental caries incidence in patients aged 18-40 years who visited the dental treatment center at East Kelayan Health Center Banjarmasin Selatan District